Legal Policy for the Formulation of Implementing Regulations on Restorative Justice in the Criminal Justice System: Kebijakan Hukum Pembentukan Peraturan Pelaksanaan Keadilan Restoratif dalam Sistem Peradilan Pidana - Hafid, Irwan; Utomo, Adhi Prasetyo (Lex Renaissance, 2026)
The regulation of restorative justice in the Criminal Procedure Code (KUHAP 2025) demonstrates a shift in legal policy within the Indonesian criminal justice system. This change not only alters the legal basis but may also affect the process of resolving criminal cases. Restorative justice has been widely studied within the context of sectoral regulations, but studies in KUHAP 2025 and the need for its implementing regulations remain limited. This study aims to examine the legal policy on restorative justice in KUHAP 2025 and the formation of its implementing regulations within the criminal justice system. This study employs a normative legal research method using conceptual and statutory approaches. Previously, restorative justice was regulated sectorally through Police Regulation Number 8 of 2021, Prosecutor Regulation Number 15 of 2020, and Supreme Court Regulation Number 1 of 2024. The decision to regulate restorative justice in KUHAP 2025 reflects a legal policy choice toward the aspired legal framework (ius constituendum), as it strengthens legality, victims’ rights, the restorative paradigm, the harmonization of the criminal justice system, and the availability of judicial control mechanisms that were not provided for in previous regulations. Furthermore, the formulation of implementing regulations on restorative justice through a Government Regulation is necessary, with due consideration given to restorative justice mechanisms at the stages of investigation, adjudication, and execution of judgments, as well as the regulation of mediators, penal mediation procedures, and the legal consequences of restorative agreements. Further research is needed to examine the implementation of restorative justice in KUHAP 2025 within the practice of criminal law enforcement in Indonesia.